Analysis of the Level of Futsal Shooting Skills at the Vamos U-19 Academy in Bengkulu City - Chindy Teza Prabowo (Sinar Sport Journal, 2021)
The problem in this study is how the basic skill level of playing futsal is shooting futsal skills at the Vamos U-19 Academy in Bengkulu City. The purpose of this study was to describe the level of futsal shooting skills at the Vamos U-19 Academy in Bengkulu City in 2021. The population in this study were all athletes on futsal shooting skills at the Vamos U-19 Academy in Bengkulu City. The sampling technique is using total sampling. The sample in this study were 24 athletes. Statistics are taken using shooting. The results showed that the description of futsal shooting skills at the Vamos U-19 Academy Bengkulu City 0 people or (0%) were in the Very Good category, 0 people were in the good category, 5 people were in the medium category, 19 people were in the poor category, 0 people are in the very poor category. So the overall level of Futsal Shooting skills at Vamos Akademi Bengkulu is in the "less" category (18.41). The results showed that there were 0 people or (0%) in the interval class <10 and below, 19 people or (79.16%%) in the 11-21 class interval, 5 people or (20.83%) in the 22-33 interval class, 0 people or (0%) are in the interval class 34-45, 0 people or (0%) are in the interval class > 46. and above.